Vocational Training for Industrial Workers - Girard, Léonce (Relations industrielles / Industrial Relations, 1951)
SummaryWhose business is it ? The State's or Industry's ? — Opinions from Paris, Romans, Brussels and Rome. — Should Quebec adopt a rigid formula ?